Pengaruh Struktur Modal, Likuiditas, dan Ukuran Perusahaan Terhadap Kinerja Keuangan Perusahaan - Sarwindah Budi Utami; Imronudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The main objective of the analysis is to evaluate the impact of capital structure (DER), liquidity (CR), and the company’s size (Total Asset) on financial performance (ROE). The methodology that is used is a quantitative one. The population consists of an industrial sub-sector company that is listed for 2019-2022 on the Indonesian Stock Exchange (BEI). Purposive sampling is the approach that was utilized to establish the sample criteria. Over the course of four years, 19 samples in all were chosen, and 76 data were collected. Researchers employ coefficients, F tests, Hausmant tests, Chow tests, and descriptive statistical tests while analyzing data. Regression analysis with panel data is one of the analytical methods employed. The Fixed Effect Model was derived from the Chow and Hausmant Test results. The statistical F test result was 0.000000 < 0.05, so the independent variables of the capital structure, liquidity, and the company size simultaneously had a significant influence on the dependent variable of financial performance. The coefficient test results showed that capital structure significantly positive improve the financial performances variable.